Rissik Street, 1889. Johannesburg - Photo: Africana Museum (My University, 2011)
An early print showing Palace Building, a well-known city land-mark today. Rissik Street was an important shopping area especially in the 'nineties. 1889.
Black and White Photograph.
Keywords: Rissik street, 1889, Palace Building, Johannesburg